Respuesta :

The given equation

x/2 = y/3 = z/4

can be broken into three separate equations which I'll call equations (A), (B) and (C)

  • x/2 = y/3 ..... equation (A)
  • y/3 = z/4 .... equation (B)
  • x/2 = z/4 .... equation (C)

We'll start off solving for z in equation (C)

x/2 = z/4

4x = 2z ... cross multiply

2z = 4x

z = 4x/2 ... divide both sides by 2

z = 2x

Now let's solve for y in equation (A)

x/2 = y/3

3x = 2y

2y = 3x

y = 3x/2

y = (3/2)x

y = 1.5x

The results of z = 2x and y = 1.5x both have the right hand sides in terms of x. This will allow us to replace the variables y and z with something in terms of x, which means we'll have some overall expression with x only. The idea is that expression should simplify to 3 if we played our cards right.

We won't be using equation (B) at all.

---------------------

The key takeaway from the last section is that

  • z = 2x
  • y = 1.5x

Let's plug those items into the expression (2x-y+5z)/(3y-x) to get the following:

(2x-y+5z)/(3y-x)

(2x-y+5(2x))/(3y-x) ..... plug in z = 2x

(2x-y+10x)/(3y-x)

(12x-y)/(3y-x)

(12x-1.5x)/(3(1.5x)-x) .... plug in y = 1.5x

(12x-1.5x)/(4.5x-x)

(10.5x)/(3.5x)

(10.5)/(3.5)

3

We've shown that plugging z = 2x and y = 1.5x into the expression above simplifies to 3. Therefore, the equation (2x-y+5z)/(3y-x) = 3 is true when x/2 = y/3 = z/4. This concludes the proof.